CD70 Deficiency Associated With Chronic Epstein-Barr Virus Infection, Recurrent Airway Infections and Severe Gingivitis in a 24-Year-Old Woman - Krüger, Renate; Martin, Emmanuel; Dmytrus, Jasmin; Feiterna-Sperling, Cornelia; Meisel, Christian; Unterwalder, Nadine; Kölsch, Uwe; Wahn, Volker; Hofmann, Jörg; Korn, Paula; Latour, Sylvain; Boztug, Kaan; et al. (Frontiers in Immunology, 2020)
Most of the few patients with homozygous CD70 deficiency described to date suffered from EBV related malignancies in early childhood. We present a women with CD70 deficiency diagnosed in adulthood. She presented in childhood with recurrent airway infections due to encapsulated bacteria, herpes zoster and a fulminant EBV infection followed by chronic EBV infection with mild lymphoproliferation and severe gingivitis/peridontal disease with high EBV viral load in saliva and gingival plaques as an adult. Up to the age of 24 years she developed no malignancy despite constant EBV viremia since primary EBV infection 15 years previously. Immunologic evaluation in childhood showed hypogammaglobulinemia with impaired polysaccharide responsiveness. She has been stable on immunoglobulin substitution with no further severe viral infections and no bacterial airway infections in adulthood. Targeted panel sequencing at the age of 20 years revealed a homozygous CD70 missense mutation (ENST00000245903.3:c.2T>C). CD70 deficiency was confirmed by absent CD70 expression of B cells and activated T cell blasts. The patient finished high school, persues an academic career and has rarely sick days at college. The clinical course of our patient may help to counsel parents of CD70 deficient patients with regard to prognosis and therapeutic options including haematopoetic stem cell transplantation.